Perilaku Asertif Siswa Korban Bullying - Reval, Reval; Karneli, Yeni (Universitas Negeri Padang, 2023)
This research is motivated by the existence of a phenomenon that occurs in many students of SMP Negeri 22 Padang who are victims of bullying. The purpose of this study is to describe how assertive behavior is viewed from the aspect of conveying something directly, assertively, positively and persistently, fairness in human relations, acting based on self-interest, being able to defend oneself, exercising personal rights, respecting the rights of others. the rights of others, to express feelings honestly and comfortably. The type of research used in this research is quantitative with descriptive methods. The sample in this study were 62 students of SMP N 22 who were victims of bullying. The data were obtained by giving instruments in the form of questionnaires to students. The results showed that the level of assertive behavior of students who were victims of bullying at SMP N 22 Padang had assertive behavior in general in the medium category, while the assertive behavior of students who were victims of bullying was based on the aspect of conveying something directly, assertively. , positive and persistent are generally in the medium category.